1999
DOI: 10.1152/ajpregu.1999.277.2.r434
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of the 20S proteasome are increased in skeletal muscle during sepsis

Abstract: Recent studies suggest that sepsis stimulates ubiquitin-dependent protein breakdown in skeletal muscle. In this proteolytic pathway, ubiquitinated proteins are recognized, unfolded, and degraded by the multicatalytic 26S protease complex. The 20S proteasome is the catalytic core of the 26S protease complex. The role of the 20S proteasome in the regulation of sepsis-induced muscle proteolysis is not known. We tested the hypothesis that sepsis increases 20S proteasome activity and the expression of mRNA for vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
70
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 31 publications
7
70
0
1
Order By: Relevance
“…In septic rats, Voisin et al (749) first observed a rise in mRNA for E2-14k, an E2 protein that mediates ubiquitin conjugation via the N-end rule pathway. Potential involvement of E2-14k was reinforced by data from Hobler et al (316) who observed that E2-14k mRNA was elevated in fast-twitch (but not slow-twitch) muscle of septic rats. Later studies confirmed upregulation of E2-14k in fasttwitch muscles of rats subjected to cecal ligation and puncture (200) or endotoxemia (113).…”
Section: A the Ubiquitin-proteasome Pathway In Critical Illnessmentioning
confidence: 94%
See 1 more Smart Citation
“…In septic rats, Voisin et al (749) first observed a rise in mRNA for E2-14k, an E2 protein that mediates ubiquitin conjugation via the N-end rule pathway. Potential involvement of E2-14k was reinforced by data from Hobler et al (316) who observed that E2-14k mRNA was elevated in fast-twitch (but not slow-twitch) muscle of septic rats. Later studies confirmed upregulation of E2-14k in fasttwitch muscles of rats subjected to cecal ligation and puncture (200) or endotoxemia (113).…”
Section: A the Ubiquitin-proteasome Pathway In Critical Illnessmentioning
confidence: 94%
“…Voisin et al (749) demonstrated that mRNA for subunits of the proteasome fluctuate in parallel with muscle proteolysis rates. Proteolytic activity of the proteasome is elevated by experimental sepsis (316), a response that involves both trypsin-and chymotrypsin-like peptidase activities (486).…”
Section: A the Ubiquitin-proteasome Pathway In Critical Illnessmentioning
confidence: 99%
“…The maintenance of Ub homeostasis is essential for cell viability, and an adequate supply of Ub is crucial for the ability of the cell to withstand stress (1)(2)(3). Under such conditions, aberrant proteins are formed in large amounts, leading to an increase in the activity of the Ub-proteasome system (UPS), which partially results from accelerated rate of synthesis of Ub and other components of the UPS (4)(5)(6). Interestingly, the total amount and ratio between free and bound Ub vary among different tissues under basal conditions (7), and significant changes occur in Ub homeostasis during different pathologies (4,8).…”
mentioning
confidence: 99%
“…Under such conditions, aberrant proteins are formed in large amounts, leading to an increase in the activity of the Ub-proteasome system (UPS), which partially results from accelerated rate of synthesis of Ub and other components of the UPS (4)(5)(6). Interestingly, the total amount and ratio between free and bound Ub vary among different tissues under basal conditions (7), and significant changes occur in Ub homeostasis during different pathologies (4,8). The mechanisms that underlie Ub regulation under different pathophysiological conditions are largely unknown.…”
mentioning
confidence: 99%
“…This experimental model was used because we (49,76) and others (29) found previously that treatment of cultured myotubes with dexamethasone resulted in increased calpain-and ubiquitin-proteasome-dependent proteolysis, similar to the situation observed in muscle wasting caused by sepsis (14,28,72,77). Cytosolic calcium concentrations were determined by fura-2 AM fluorescence, and SOCE was measured by using calcium "add-back" to muscle cells after depletion of calcium stores.…”
mentioning
confidence: 99%